Volitional Control of Neuromagnetic Coherence - Sacchet, Matthew D.; Mellinger, Jürgen; Sitaram, Ranganatha; Braun, Christoph; Birbaumer, Niels; Fetz, Eberhard (Frontiers in Neuroscience, 2012)
Coherence of neural activity between circumscribed brain regions has been implicated as an indicator of intracerebral communication in various cognitive processes. While neural activity can be volitionally controlled with neurofeedback, the volitional control of coherence has not yet been explored. Learned volitional control of coherence could elucidate mechanisms of associations between cortical areas and its cognitive correlates and may have clinical implications. Neural coherence may also provide a signal for brain-computer interfaces (BCI). In the present study we used the Weighted Overlapping Segment Averaging (WOSA) method to assess coherence between bilateral magnetoencephalograph (MEG) sensors during voluntary digit movement as a basis for BCI control. Participants controlled an onscreen cursor, with a success rate of 124 of 180 (68.9%, sign-test p < 0.001) and 84 out of 100 (84%, sign-test p < 0.001). The present findings suggest that neural coherence may be volitionally controlled and may have specific behavioral correlates.